2019
DOI: 10.3390/molecules24061112
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Fermented Black Garlic Exhibit a Hepatoprotective Effect on Acute Hepatic Injury

Abstract: The mechanism of hepatoprotective compounds is usually related to its antioxidant or anti-inflammatory effects. Black garlic is produced from garlic by heat treatment and its anti-inflammatory activity has been previously reported. Therefore, the aim of this study was to investigate the hepatoprotective effect of five different extracts of black garlic against carbon tetrachloride (CCl4)-induced acute hepatic injury (AHI). In this study, mice in the control, CCl4, silymarin, and black garlic groups were orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Other benefits of AGE include improved lipid profiles and gut microbiota. In another study, fermented raw garlic at a concentration of 200 mg/kg exhibited hepatoprotective effect, which was evident in terms of reduced aminotransferase (AST) and alanine aminotransferase (ALT) levels in hepatic cells of Sprague‐Dawley rats (Tsai et al., 2019). However, the effects of black ginseng and black garlic at various doses on blood sugar, serum fat, and NAFLD have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Other benefits of AGE include improved lipid profiles and gut microbiota. In another study, fermented raw garlic at a concentration of 200 mg/kg exhibited hepatoprotective effect, which was evident in terms of reduced aminotransferase (AST) and alanine aminotransferase (ALT) levels in hepatic cells of Sprague‐Dawley rats (Tsai et al., 2019). However, the effects of black ginseng and black garlic at various doses on blood sugar, serum fat, and NAFLD have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…2-Propen-1-ol was generated by thermal degradation of alliin and its biochemical precursor deoxyalliin [24]. Yu et al [9] proposed a [2,3]-sigmatropic rearrangement mechanism for 2-propen-1-ol formation from alliin. Furthermore, as noted by Rizzi [25], 2-propen-1-ol might react with allylthio radicals, allyl mercaptan, or alliin/deoxyalliin to give diallyl sulfide.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic (Allium sativum L.) is native to Western and Central Asia, and it has been cultivated and consumed extensively for centuries because of its medicinal and edible value [1]. The various biological activities of garlic extract include antioxidant, anticancer, antihypertensive, and age-resisting activities, and they have attracted increasing interest [2][3][4]. Additionally, processed garlic products in the domestic seasoning market, including fried garlic oil, have been applied in a variety of food products, such as chips, breads, and instant noodles, as a flavor ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of SOD, GSH-Px were decreased with an increase in the levels of alanine transaminase (ALT), aspartate transaminase (AST), lactate dehydrogenase, and alkaline phosphatase (ALP) [112]. In another study, Tsai et al [28] demonstrated that the administration of SAC and polysaccharides enriched-BG extract into ICR mice inhibited CCl 4 -induced hepatic injury by inhibiting lipid peroxidation and inflammation. Moreover, Kim et al [113] demonstrated the hepatoprotective effects of aged black garlic on chronic-induced liver injury in Sprague-Dawley rats due to the suppressive effects of aged black garlic extract on cytochrome P450 2E1 activity and its inductive effect on glutathione-s-transferase and quinone reductase activities.…”
Section: Effects Of Black Garlic On Digestive Diseases 631 Black Garlic and Liver Diseasesmentioning
confidence: 99%